Radical black theatre in the New Deal - Dossett, Kate (John Hope Franklin series in African American history and culture., 2020)
"Between 1935 and 1939, the United States government paid out-of-work artists to write, act, and stage theatre as part of the Federal Theatre Project (FTP), a New Deal job relief program. In segregated 'Negro Units' set up under the FTP, African American artists took on theatre work usually reserved for whites, staged black versions of 'white' classics, and developed radical new dramas. In this fresh history of the FTP Negro Units, Kate Dossett examines what she calls the black performance community-a broad network of actors, dramatists, audiences, critics, and community activists-who made and remade black theatre manuscripts for the Negro Units and other theatre companies from New York to Seattle"--